2012
DOI: 10.4236/ajps.2012.38139
|View full text |Cite
|
Sign up to set email alerts
|

Control of Leaf Spot Diseases on Ecotypes of Faba Bean (<i>Vicia faba</i> L.) Produced in the Andean Region of Bolivia

Abstract: The basin of Lake Titicaca is a faba bean-producing microregion of Bolivia where the crop is destined for export. The most commonly cultivated ecotypes "Gigante de Copacabana" and "Usnayo" are affected by diseases that can cause production losses. The aims of the present work were to identify the causal agents of leaf spot affecting these ecotypes, to record disease intensity levels, and to estimate their effect on production. In 2004 and 2005, leaflet, stem and pod samples were taken from faba bean plants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…B. fabae is viewed as the primary causal agent of chocolate spot disease. Several reports (Harrison, 1988;Coca-Morante, Mamani-Álvarez, 2012;Bilkiss et al, 2019) have mentioned B. cinerea as a pathogen of faba bean either separately or within a complex with B. fabae. Zhang et al (2010) identified and described the third species of Botrytis from faba bean in China -B. fabiopsis.…”
Section: Introductionmentioning
confidence: 99%
“…B. fabae is viewed as the primary causal agent of chocolate spot disease. Several reports (Harrison, 1988;Coca-Morante, Mamani-Álvarez, 2012;Bilkiss et al, 2019) have mentioned B. cinerea as a pathogen of faba bean either separately or within a complex with B. fabae. Zhang et al (2010) identified and described the third species of Botrytis from faba bean in China -B. fabiopsis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the application of different T. harzianum strains under field conditions resulted an increase of yield from 8-30% beside acting as the biocontrol agents of chocolate spot [10]. Seed treatment of bio-agents combined with foliar treatments were more effective for controlling leaf spot of faba bean than foliar spray only [11]. Moreover, a mixture of Rhizobium leguminosarum and T. viride tag4 as seed treatment and foliar spray increased the yield by 23% compared to the uninoculated control plants beside controlling chocolate spot [3].…”
Section: Introductionmentioning
confidence: 99%